Foreign aid and economic development in postwar Lebanon - Ghassan Dibeh (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2007)
This paper shows that foreign aid in postwar Lebanon passed through two phases with distinct features that have had far reaching implications for postwar development. In the first phase lasting from 1992-97, foreign aid was mainly channelled towards providing resources for postwar reconstruction projects. The second phase from 1997 to the present witnessed a qualitative shift in foreign aid utilization from reconstruction needs towards financial stability and balance-of-payments equilibrium needs. This shift allowed the government to intervene in the foreign exchange market, maintained balance of payments surpluses during this period, reduced interest rates on public debt instruments and finally provided the necessary liquidity and 'confidence' for the government to continue borrowing funds from local commercial banks and foreign investors. More importantly this shift in foreign aid allowed the government to avoid financial and currency crises in 2002. However, the cost of such a qualitative shift was large in terms of fiscal management, diversion of funds from reconstruction, and the increased dependency of the Lebanese economy on foreign aid for stabilization purposes.
Keywords: D74; E52; O23; H56; 330; foreign aid; postwar reconstruction; post-conflict; Lebanon; Internationale Wirtschaftshilfe; Kriegsfolgen; Libanon